The Effect of Field‐Aligned Currents and Centrifugal Forces on Ionospheric Outflow at Saturn. Issue 7 (16th July 2020) - Martin, C. J.; Ray, L. C.; Felici, M.; Constable, D. A.; Lorch, C. T. S.; Kinrade, J.; Gray, R. L.
Abstract: Ionospheric outflow is driven by an ambipolar electric field induced due to the separation of electrons and ions in a gravitational field when equilibrium along a magnetic field line is lost. A model of ionospheric outflow at Saturn was developed using transport equations to estimate the number of charged particles that flow from the auroral regions into the magnetosphere. The model evaluates the outflow from 1, 400 km in altitude above the 1 bar level, to 3 R S along the field line. The main ion constituents evaluated are R + and R 3 + . We consider the centrifugal force exerted on the particles due to a fast rotation rate, along with the effects of field‐aligned currents present in the auroral regions. The total number flux from both auroral regions is found to be 5.5–13.0×10 27 s −1, which relates to a total mass source of 5.5–17.7 kg s −1 . These values are on average an order of magnitude higher than expected without the additional effects of centrifugal force and field‐aligned currents. We find the ionospheric outflow rate to be comparable to the lower estimates of the mass loading rate from Enceladus and are in agreement with recent Cassini observations. This additional mass flux into the magnetosphere can substantially affect the dynamics and composition of the inner and middle magnetosphere of Saturn. Key Points: An ionospheric outflow model is developed for use at Saturn's auroral regions The presence of field‐aligned currents and centrifugal forces enhances outflow by an order of magnitude Predicted total outflow flux rate of 5.5–13.0×10 27 s −1 is comparable to flux calculated from Cassini data